The influence of the credit agreement process and service quality on customer retention moderated by customer satisfaction at PT. WOM Finance, Tangerang Regional Banten branch - Fathurrozi, Fathurrozi; Haryono, Budi (Enrichment : Journal of Management, 2025)
This study investigates the influence of the credit contract process and service quality on customer retention, with customer satisfaction serving as a moderating variable, in the context of PT WOM Finance, Tangerang Branch. The problem of low customer retention is presumed to stem from procedural non-compliance in credit contracts and inadequacies in service quality. Employing a quantitative approach, the study utilizes Structural Equation Modeling–Partial Least Squares (SEM-PLS) with data collected from 85 respondents. The findings reveal that both the credit contract process and service quality exert a significant effect on customer retention. Notably, customer satisfaction does not moderate the relationship between the credit contract process and customer retention; however, it significantly moderates the relationship between service quality and customer retention. These results underscore the critical role of enhancing procedural rigor in credit agreements and optimizing service delivery to foster customer loyalty. The implications of this study provide valuable insights for PT WOM Finance and other financial institutions in formulating strategies aimed at improving contract management and service quality to strengthen customer satisfaction and long-term retention in an increasingly competitive financial services industry